(untitled) (Bangladesh Journal of Agricultural Research, 2020)
Ant community serves as an bioindicator on the assumption that the extent of ant diversity reflects broader ecosystem change. Bangladesh with varied agro ecosystem providing broad ecological niche of diversified ant community. The study of ant community is a way to measure the recent transformation of agro ecosystems in Bangladesh to provide information about management and conservation of agricultural landscape. The present study was conducted in Bhawal National Park to delve deeper into the diversity and richness of ants as they work as ecological indicators of an ecosystem. Being a conservation site with natural resources, Bhawal National Park can serve as study site with species diversity due to having sites with similar vegetation and soil type, but different ecological parameters. The objective of the study was to identify local ant fauna in forest agroecosystem to understand the impact on human disturbance to ant communities of the study area. Total 399 individuals were identified from 42 species of 17 genera belonging to 6 subfamilies. Sampling was performed using Time unit sampling (TUS) and pitfall trap in two different areas, viz, area 1 and 2. The most dominant subfamily of the study area was Myrmicinae. The highest number of species were found from the genus Camponotus. The Shannon-Wiener’s Diversity Index showed that area 1 had higher species diversity due to favorable living conditions with less animal intervention and higher density of vegetation playing key role. However, the species dissimilarity in different study areas were relatively low due to similar vegetation and soil type. The study provided an inventory of Bangladesh as well as identification system of ants. This is the first comprehensive list of ants from forest ecosystem of Bangladesh. Bangladesh J. Agril. Res. 44(4): 679-688, December 2019